Method of regulating power quality indicators - Anton Panov (Challenges and Issues of Modern Science)
One of the important requirements for electricity supply is ensuring the quality of electricity, which is understood as the degree of compliance of quality indicators with accepted standards. Deviation of voltage and other quality indicators from established norms significantly affects the operation of electrified equipment and electrical networks, which leads to electromagnetic and technological components of economic damage. Also, voltage asymmetry is one of the urgent problems of 0.4 kV three-phase electrical networks. The asymmetry of the voltage is manifested in the inequality between the models of the phase voltage vectors and the shift angles between them.